The effects of parent education program on the state anxiety levels of parents of first graders - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
The first year of school is an important beginning which involves critical processes, as it determines how a new school-child will perceive the concepts of school, learning, and teacher and the effects of this perception may affect future school success. This new beginning may increase the stress levels of both children and parents. Starting school does not mean that parents transfer their role of educator entirely to the teacher; instead, education should be handled jointly at home and school. To enable this, parents need to be educated too. As such an education would raise the awareness levels of parents, it may also decrease their anxiety levels. In this study, the state anxiety levels of 61 parents with a child who has just started the first grade were measured before and after the parent education program and it was found that the program was effective. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Starting school; first graders; parent education program; orientation; state anxiety